System analysis of efficient production processes for productivity enhancement through productivity balance in injection moulding process - Usubamatov, Ryspek, Prof. Dr.; Mohd Sapuan, Salit, Prof. Ir. Dr.; Megat Mohamad Hamdan, Megat Ahmad, Assoc. Prof. Dr.; Napsiah, Ismail, Assoc. Prof. Datin Dr. (The Institution of Engineers, Malaysia, 2011)
Link to publisher's homepage at http://www.myiem.org.my/